Proposals for improving the research efficiency in goats - Morand-Fehr, P.; Lebbie, S.H.B. (Elsevier, 2004)
Presently, research on goats is less developed than on cattle, sheep and pigs in spite of the world-wide significance of goat farming. In the year 2000, the countries with low levels of income produced 33% of all technical papers published on goats around the world, while having 81% of the world goat population. The countries with high levels of income produced 46% of all goat papers for only 1% of the world goat population. Generally, the quality and efficiency of goat research is very variable, although the situation has improved during the last 20 years. Despite limited financing support for goat research, its efficiency could be improved by a better research organisation and implementing committees, which include representatives of professional organisations to decide research priorities, and by implementing research networks, which would incite researchers from various institutions to work together. Such research networks must supply new general, scientific knowledge by pooling the results obtained from various experimental conditions with linkage analyses particularly if the bibliographic results appear to be heterogeneous or conflicting. Organisations for analysing and synthesising the scientific information must be created in order to make it easier for application by end users. Moreover, strong efforts must be made to improve the professional training of researchers in the goat sector. A project for improving the structuring of goat research at the world-wide level must be supported by international organisations such as FAO, ICARDA, ILRI, IGA, etc. Difficulties encountered by goat research are the same as those of the other animal species but in the goat sector the consequences are more significant because of its delayed development and very limited organisation.